Synthesis and characterization of PVA-based binary-gel electrolytes including massive ions - Ozturk, Tugce Pinar; Gelir, Ali; Keshtiban, Nahid Aghabalapoor; Yargi, Onder; Ozdemir, Onur B.; Mucur, Selin Piravadili; Secgin, Alper (Springer, 2023)
The motion of the ion pairs under the applied electric field is an important phenomenon in the storage properties of the capacitive devices. In this study, two different molecules, 1,3,6,8-pyrenetetrasulfonic acid tetrasodium salt hydrate (P-4) and tetra-alkyl ammonium bromide (TAAB), were used as ionic groups in the PVA gel electrolytes. The counter ions of P-4 and TAAB are Na+ and Br- and their masses (about 23 and 80 g/mole) are much smaller than the masses of their host molecules P-4(-4) and TAAB(+1) (about 524 and 322 g/mole). Three different PVA gel electrolytes in slab configurations were synthesized and characterized: PVA gel electrolyte including only P-4, only TAAB, and mixture of these ionic groups. The binary system was obtained by putting the gel electrolyte including TAAB on the gel electrolyte including P-4. cyclic voltammetry (CV), and galvanostatic charge discharge (GCD) techniques were used to characterize the electrolytes. The results of the proposed binary gel polymer electrolyte were compared with single and mixture electrolytes. It was observed that since P-4 and TAAB host molecules are highly massive, they can shield some part of the counter ions when an electric field was applied. In addition, the agglomeration of the TAAB molecules in the PVA matrix causes trapping the counter ions in the dense regions and prevents the motion of the counter ions under the applied field and then induces the increasing internal resistance. Therefore, the effective mass of TAAB molecules increases considerably, and when an electric field is applied, they move slowly.
Keywords: Polymer gel electrolytes; Massive ions; Ion transport; Binary electrodes; Pyrenetetrasulfonic acid tetrasodium salt; Tetra-alkyl ammonium bromide